Direct Identification of Acetaldehyde Formation and Characterization of the Active Site in the [VPO4].+/C2H4 Couple by Gas‐Phase Vibrational Spectroscopy. Issue 52 (8th November 2019) - Li, Ya‐Ke; Debnath, Sreekanta; Schlangen, Maria; Schöllkopf, Wieland; Asmis, Knut R.; Schwarz, Helmut
Abstract: The gas‐phase reaction of the heteronuclear oxide cluster [VPO4 ] .+ with C2 H4 is studied under multiple collision conditions at 150 K using cryogenic ion‐trap vibrational spectroscopy combined with electronic structure calculations. The exclusive formation of acetaldehyde is directly identified spectroscopically and discussed in the context of the underlying reaction mechanism. In line with computational predictions it is the terminal P=O and not the V=O unit that provides the oxygen atom in the barrier‐free thermal C2 H4 →CH3 CHO conversion. Interestingly, in the course of the reaction, the emerging CH3 CHO product undergoes a rather complex intramolecular migration, coordinating eventually to the vanadium center prior to its liberation. Moreover, the spectroscopic structural characterization of neutral C2 H4 O deserves special mentioning as in most, if not all, ion/molecule reactions, the neutral product is usually only indirectly identified. Abstract : Caught in the act : The gas‐phase reaction of the heteronuclear oxide cluster [VPO4 ] .+ with C2 H4 was studied by infrared photodissociation spectroscopy, which directly identified the formation of acetaldehyde and revealed the terminal P=O moiety as the active site of [VPO4 ] .+ in the oxygen atom transfer (OAT) reaction with ethylene, in line with theoretical predictions.